1986
DOI: 10.1002/path.1711480404
|View full text |Cite
|
Sign up to set email alerts
|

The significance of myocardial bridge upon atherosclerosis in the left anterior descending coronary artery

Abstract: The relation between myocardial bridges (MB) and atherosclerosis in the left anterior descending coronary artery (LAD) was explored using morphometric methods in 642 hearts. The location of myocardial bridges in the LAD was classified according to distribution as proximal, middle and distal. Myocardial bridges were found in 48 per cent of males and 36 per cent of females. When proximal myocardial bridging was present intimal thickening and macroscopic raised lesion were increased just before the bridge as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 21 publications
8
92
1
4
Order By: Relevance
“…Similar to previous autopsy,1, 16 angiographic,5 and multidetector computed tomography17 reports, we found a greater plaque burden in the LAD segment proximal to the MB than within the tunneled LAD segment. This preferential location of atherosclerotic plaque in relation to the MB is attributed partially to hemodynamic disturbances caused by MB muscle contraction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous autopsy,1, 16 angiographic,5 and multidetector computed tomography17 reports, we found a greater plaque burden in the LAD segment proximal to the MB than within the tunneled LAD segment. This preferential location of atherosclerotic plaque in relation to the MB is attributed partially to hemodynamic disturbances caused by MB muscle contraction.…”
Section: Discussionsupporting
confidence: 91%
“…These adverse effects likely result from 2 distinct mechanisms: (1) accelerated plaque formation in the segment proximal to the MB, as investigated in the current study, and (2) alteration in the effective blood perfusion of the affected myocardial territory owing to delayed arterial relaxation in diastole or the Venturi effect on the septal branches that can cause functional ischemia of the septal wall 4. Furthermore, external systolic compression and endothelial dysfunction frequently observed in the tunneled artery could stimulate coronary vasospasm and platelet aggregation resulting in acute coronary syndrome in certain clinical settings 16, 21, 23, 24…”
Section: Discussionmentioning
confidence: 86%
“…Endothelial cell permeability was found to be increased in atherosclerotic epicardial segments of hypercholesterolemic rabbits, but not within myocardial bridges (11). Other studies indicated that the intimal layer of a bridge is spared from foam cells and synthetic-type vascular smooth muscle cells, which precipitate plaque formation (12). At the molecular level, the association among the expression of Myocardial bridging constitutes a congenital, usually benign, coronary abnormality defined as a segment of a major epicardial coronary artery that follows an intramural course through the myocardium.…”
Section: Evidence Of Absence Of Atherosclerosis Within Myocardial Brimentioning
confidence: 95%
“…Even though the relationship between endothelial dysfunction and arteriosclerosis has been described in clinical conditions such as diabetes and hypercholesterolemia, endothelial dysfunction restricted to the site of mechanical compression may reflect the proatherogenic effect, even if modest, in this particular type of endothelial dysfunction. This hypothesis needs to be validated [16][17][18][19][20].…”
Section: Endothelial Dysfunction and Absence Of Arteriosclerosis: An mentioning
confidence: 99%